Doping Effect and Microstructure Behavior of Rare-Earth Element Cerium (Ce+3) in Barium Hexaferrite (BaCexFe12-xO19) Nanoparticles - Gilani , Zaheer Abbas; Ahmed, Awais; Khan Asghar, H M Noor ul Huda; Muhammad Khalid (Journal of Materials and Physical Sciences, 2020)
Cerium substituted BaM hexaferrites BaCexFe12-xO19 (x = 0.0, 0.25, 0.5, 0.75, and 1.0) nano crystallites were synthesized via Sol-gel method. The x-ray diffraction (XRD) patterns were analyzed by Rietveld refinement which confirms the formation of hexagonal structure. The crystalline size was calculated by Debye Scherrer method, W–H method and SSP method. The lattice constant ? found to decrease, this was due to the octahedral site replacing a large radius of Ce3+ ion with a smaller radius Fe3+ ion, While the lattice constant c found increase. The x-ray density observed increases with increasing Ce3+ concentration. Fourier transform infrared spectroscopy (FTIR) confirmed the two frequency bands n1 tetrahedral site and n2 octahedral site in a range between 400–620 cm-1. Impedance analyzer was used to investigate the dielectric properties in a range of 1 MHz – 3 GHz following Maxwell Wagner model. Dielectric constant showed decreasing trend while dielectric loss showed dispersive behavior by increasing frequency and same was that with tangent loss, such behavior was due to Koop's phenomenological theory. AC conductivity exhibits a plane behavior in a low frequency, while dispersive in high frequency. Such behavior was due to grain effect at high frequency. Impedance showed continuous action at high frequency, which is attributed to the release of space charges. The real and imaginary modulus showed variation by increasing frequency, which was due to the occurrence of relaxation phenomenon. As per dielectric research, these ferrites can be utilized in high frequency devices, microwave technologies, and semiconductor devices.